Vaginitis: Making Sense of Over-the-Counter Treatment Options - Lauren B. Angotti; Lara C. Lambert; David E. Soper (Hindawi Limited, 2007)
Background. The FDA approved over-the-counter (OTC) use of vaginal antifungals in 1990. Subsequently, a plethora of OTC products have become available to women on drugstore shelves. Objectives. The purpose of this study was to determine the availability of OTC products marketed for the treatment of vaginitis and to determine if their efficacy had been confirmed by published prospective randomized control trials (RCTs). Materials and methods. The authors chose four retail locations frequented by women seeking vaginitis treatment. All products deemed a viable treatment option were purchased. Results. All intravaginal imidazoles purchased, regardless of treatment duration or active ingredient, were found to be of proven efficacy. We were unable to find an RCT confirming the effectiveness of vaginal anti-itch creams and homeopathic treatments for vaginitis. Conclusion. 45% of products available to women in the feminine hygiene section of the stores surveyed could not be confirmed to be effective for treating infectious vaginitis.